Customer decision making vis-à-vis halal branding - Mohd. Israil, Khaliq Ahmad (Malaysian Institute of Management, 2013)
Understanding the preference of Muslim youth for halal (religiously permissible)certified products in their search for branded items was the underlying motive behind this research. Since sportswear brand owners usually target youth market segments, Muslim youth in the Malaysian market were selected as the main respondents for this study. The collective perceptions of quality, brand awareness, brand association and consumer loyalty constitute brand equity and this study focused on brand equity research in the Malaysian marketing environment.